2007
DOI: 10.1016/j.bbadis.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Motor behavioral and neuropathological deficits in mice deficient for normal prion protein expression

Abstract: It has been difficult to reconcile the absence of pathology and apparently normal behavior of mice lacking prion protein (PrP), referred to as Prnp(0/0) mice, with a mechanism of prion pathogenesis involving progressive loss of PrP(C)-mediated neuroprotection. However, here we report that Prnp(0/0) mice exhibit significant age-related defects in motor coordination and balance compared with mice expressing wild type Prnp on a syngeneic background, and that the brains of behaviorally-impaired Prnp(0/0) mice disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
6
39
0
1
Order By: Relevance
“…Thus, differing results in such tests were absent between wild-type and PrP C -null genotypes at 8 -12 weeks of age, but apparent in older animals (60,61). Other groups also reported age-dependent motor deficits restricted to aged PrP C -null mice (62, 63).…”
Section: Discussionmentioning
confidence: 81%
“…Thus, differing results in such tests were absent between wild-type and PrP C -null genotypes at 8 -12 weeks of age, but apparent in older animals (60,61). Other groups also reported age-dependent motor deficits restricted to aged PrP C -null mice (62, 63).…”
Section: Discussionmentioning
confidence: 81%
“…This finding has now been extended to the early development of Prnp 0/0 mice, which display deficits in motor coordination and balance and vacuolation in several WM tracts at age 6 months. 29 In the human brain, pathologic studies of terminal CJD reported axonal damage, and suggested the possibility of retrograde axonal transport of prions, infecting multiple sites along neuroanatomic pathways. 27,[30][31][32] In the Japanese panencephalopathic variant (pCJD), WM damage has been noted in the internal capsule, brain stem, and middle cerebellar peduncles, 33 consistent with our imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Other than resistance to prion infection, 8 these animals display only marginal, if any, phenotypes in lifespan, development or behavior. 9,10 On the other hand, the possibility exists that a hidden phenotype becomes manifest only under defined stress conditions. However, the conservation of PrP C in the vertebrate sub-phylum and its ubiquitous tissue expression, argue against the possibility that PrP C may have been evolutionarily selected to only enable the onset and transmission of these fatal brain disorders.…”
Section: Promotes Regeneration Of Adult Skeletal Musclementioning
confidence: 99%